Hippocampal Volume and Entorhinal Cortex Thickness in Alzheimer’s Disease - Leon Agung Manurung; Widiana Ferriastuti; Bambang Soeprijanto; Hartono Yudi Sarastika (Institute of Medico-legal Publications Pvt Ltd, 2022)
Magnetic Resonance Imaging (MRI) is the standard imaging evaluations in Alzheimer’s Disease (AD).Information regarding hippocampus and entorhinal cortex sizes plays an important role in Alzheimer’sdisease. This study aims to determine hippocampal volume and entorhinal cortex thickness inAlzheimer’s disease obtained from a group of patients who underwent head MRI.This study was an observational study with retrospective approach in patients who were diagnosedwith AD and had available head MRI examination results. A total of 14 patients were diagnosed by aneurologist with AD using MMSE, Hachinsky, and NIA-AA criteria.From head MRI measurement in AD patients, we found that the mean volume of right, left, andtotal hippocampal was 1700±0.395 cm3; 1.670±0.349 cm3; and 3.370±0.725 cm3, respectively. Themean thickness of right, left, and total entorhinal cortex was 1.821±0.459 mm; 1.463±0.369 mm; and3.285±0.791 mm, respectively. There is a possible difference between the early and late stages of AD inthe same patient. Further studies with larger cohorts are needed to examine these correlations.